2022
DOI: 10.3389/fmicb.2022.906026
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Dinotefuran, Thiacloprid, and Imidaclothiz Neonicotinoids in Water Using a Novel Pseudomonas monteilii FC02–Duckweed (Lemna aequinoctialis) Partnership

Abstract: Neonicotinoids (NEOs) are the most widely used insecticides in the world and pose a serious threat to aquatic ecosystems. The combined use of free-floating aquatic plants and associated microorganisms has a tremendous potential for remediating water contaminated by pesticides. The aim of this study was to determine whether plant growth-promoting bacteria (PGPB) could enhance the phytoremediation efficiency of duckweed (Lemna aequinoctialis) in NEO-contaminated water. A total of 18 different bacteria were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Phytoremediation is an emerging biological technology that aids in the removal of harmful pollutants from water bodies and soil; however, research on phytoremediation requires a comprehensive understanding of processes and mechanisms . Duckweed, as a globally widespread aquatic plant, is attractive for phytoremediation of pollutants in water bodies (Hu et al, 2021;Walsh et al, 2021;Cai et al, 2022). Studies have…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoremediation is an emerging biological technology that aids in the removal of harmful pollutants from water bodies and soil; however, research on phytoremediation requires a comprehensive understanding of processes and mechanisms . Duckweed, as a globally widespread aquatic plant, is attractive for phytoremediation of pollutants in water bodies (Hu et al, 2021;Walsh et al, 2021;Cai et al, 2022). Studies have…”
Section: Discussionmentioning
confidence: 99%
“…Phytoremediation is an emerging biological technology that aids in the removal of harmful pollutants from water bodies and soil; however, research on phytoremediation requires a comprehensive understanding of processes and mechanisms ( Huang D, et al, 2021 ). Duckweed, as a globally widespread aquatic plant, is attractive for phytoremediation of pollutants in water bodies ( Hu et al., 2021 ; Walsh et al., 2021 ; Cai et al., 2022 ). Studies have revealed that duckweed has a great potential in the bioremediation of eutrophic water bodies, heavy metals, antibiotics, insecticides, and organic pollutants ( Ceschin et al., 2020 ; Yang et al., 2020a ; Farid et al., 2022 ; Maldonado et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%